The Obama nation leftist politics and the cult of personality - Corsi, Jerome R (New York Threshold Editions/Simon & Schuster, 2008)
Barack Obama stepped onto the national political stage when the then-Illinois State senator addressed the 2004 Democratic National Convention. Soon after Obama was elected to the U.S. Senate, author Jerome Corsi began researching Obama's personal and political background. This book is the result of that research. By tracing Obama's career and influences from his early years in Hawaii and Indonesia, the beginnings of his political career in Chicago, his voting record in the Illinois legislature, his religious training and his adoption of Christianity through to his recent involvement in Kenyan politics, his political advisors and fundraising associates and his meteoric campaign for president, Corsi shows that an Obama presidency would, in his words, be "a repeat of the failed extremist politics that have characterized and plagued Democratic Party politics since the late 1960s."--From publisher description
Preface Who I am and Why I wrote this book -- Introduction -- pt. 1 Roots -- 1 Myths from his father -- 2 Strangers in strange lands -- 3 Black rage, drugs, and a Communist mentor -- 4 Kenya, Odinga, Communism, and Islam -- pt. 2. The making of a radical politician -- 5. The ideology of "change" -- 6 Tony Rezko and "The Chicago way" -- 6 Meet Reverend Wright -- pt. 3. The candidate is the message -- 8. The cult of personality -- 9. A far-left domestic policy -- 10 Obama's antiwar, anti-Israel foreign policy -- Conlcusion Defeating Obama -- Notes -- Index
Includes bibliographical references (p. 305-339) and index
This title is also available as an eBook
1
Keywords: Obama, Barack -- Influence; Obama, Barack -- Political and social views; Obama, Barack -- Public opinion; Left-wing extremists -- United States; Personality -- Political aspects -- United States; Presidential candidates -- United States; Presidents -- United States -- Election -- 2008; Public opinion -- United States; Right and left (Political science); United States -- Politics and government -- 2001-2009